Using Critical Media Literacy (CML) to Promote Students’ Critical Awareness in a 10th Grade EFL Class in the East of Antioquia (2020)
ABSTRACT: This document reports on an action research project developed through a 10-week term intended to explore how a critical media literacy (CML) unit could foster critical awareness about gender issues depicted in media. The participants were 33 tenth grade students of a public institution in Eastern Antioquia. Data were collected through researcher journals, class artifacts, and surveys and analyzed using a qualitative approach. The results suggest that students started a process of decoding gender issues portrayed in media and became more interested in learning English through the analysis of social issues. Accordingly, this research showed that thinking and acting critically entails a process of production so that awareness does not stay at the level of decoding media messages.